The determinants of effective inter-organization information sharing in the health capital planning process. Issue 4 (July 2022) - Kashef Al-Ghetaa, Rayeh; Daniel, Imtiaz; Shaw, James; Klein, David; Brown, Adalsteinn
This qualitative study examines the determinants of effective inter-organization information sharing in the Health Capital Planning process (the process), primarily in the final stage of the process which focuses on the review of final expenses and release of a holdback. Using thematic analysis and building off a scoping review that was conducted in preparation for this study, we provide a framework for effective information sharing during the process. We interviewed 17 leaders from the Government of Ontario and hospitals across the province. The results of the interviews indicate that the most essential determinants of effective inter-organization information sharing in the process: organizational characteristics; reducing complex bureaucracies; preserving human resources and expertise; clear and standardized information; reducing policy changes; networks; negotiation abilities; information technology; training; record retention; and early planning. This study confirmed the need for effective intra-organization and interpersonal information sharing to achieve successful inter-organization information sharing.